(untitled) (Research, Society and Development, 2025)
Drug counterfeiting in Brazil represents a growing problem with a significant impact on public health, compromising therapeutic efficacy, patient safety, and public trust in health surveillance systems. The objective of this study was to present updated data on drug counterfeiting in the country, highlighting its consequences for public health, based on information from regulatory bodies such as ANVISA, as well as recent scientific evidence. Through a narrative review, national and international secondary sources were analyzed, including scientific articles, official reports, institutional databases, and technical documents published in the last ten years. The findings indicate that counterfeit drugs may contain inappropriate substances, incorrect dosages, or lack of active ingredients, leading to therapeutic failures, worsening of diseases, and increased microbial resistance. The expansion of e-commerce, socioeconomic vulnerability, and gaps in oversight are factors that facilitate the dissemination of these products in Brazil. In addition to health damage, counterfeiting causes economic losses to the pharmaceutical sector and directly affects the credibility of health institutions. Given this scenario, the need for integrated actions between the government, health professionals, and society is highlighted, involving awareness campaigns, rigorous oversight, and the adoption of traceability technologies, such as the National Drug Control System (SNCM). It is concluded that coordinated and continuous strategies are essential to reduce the circulation of counterfeit medicines and ensure greater safety and confidence in the use of medicines in the country.